Ethics of Social Media from Maqashid Syari'ah Perspective - Farida, Siti; Faozan, Akhmad (International Proceedings of Nusantara Raya, 2022)
Nowadays, social media can replace communication interactions in the real world to cyber interactions. but the large amount of content circulating on social media contains insults, hate speech against SARA differences, blasphemy against political choices, causes society to be polarized and overrides ethics in social media. Humanitarianly the content is troubling, frightening and deprives people of freedom of choice, religion, and opinion. So, the purpose of this study is to formulate the concept and application of ethics in social media in accordance with Maqashid Syariah. Qualitative research with this descriptive approach uses observational and documentation data collection techniques. This research examines how social media ethics with the perspective of Maqashid Syariah (religion, soul, reason, descendants, and property) can maintain and find their position to build social media activities based on Islamic values in creating benefits for all mankind.